The development needs of newly appointed senior school leaders in Abu Dhabi, UAE. Issue 1 (2017) - Vuuren, Nelius Jansen Van; Sayed, Yusuf
For many years the essential role that senior school leaders play in school leadership teams, and the development programmes they follow to ensure effective strategic leadership in schools have been the subject of intense debate. Crucial to this debate has been the focus on context-shaped professional learning and leadership approaches where the importance of appropriate, multifaceted, developmental support initiatives for young newly appointed senior school leaders, namely vice-principals and principals, is highlighted and recommended. This paper shows how new young Emirati senior leaders generally lack role experience and thus rely on their expat vice-principals or head of faculties for much of their daily leading strategically and operational management functions in the school. Reflecting on findings developed in a recent doctoral study, the paper highlights what 20 young newly appointed senior school leaders at the Abu Dhabi Education Council (ADEC), United Arab Emirates (as a unique group of young newly appointed leaders) say about their development needs and what specific preparation they require. This paper employed a mixed-method approach to gather data, with the findings relying heavily of a quantitative analysis of questionnaires conducted.